Comprehensive assessment of occupational exposure to microbial contamination in waste sorting facilities from Norway - Viegas, Carla; Eriksen, Elke; Gomes, Bianca; Dias, Marta; Cervantes, Renata; Pena, Pedro; Carolino, Elisabete; Twarużek, Magdalena; Caetano, Liliana Aranha; Viegas, Susana; Graff, Pål; Afanou, Anani Komlavi; et al. (Frontiers in Public Health, 2023)
Introduction It is of upmost importance to contribute to fill the knowledge gap concerning the characterization of the occupational exposure to microbial agents in the waste sorting setting (automated and manual sorting). Methods This study intends to apply a comprehensive field sampling and laboratory protocol (culture based-methods and molecular tools), assess fungal azole resistance, as well as to elucidate on potential exposure related health effects (cytotoxicity analyses). Skin-biota samples (eSwabs) were performed on workers and controls to identify other exposure routes. Results In personal filter samples the guidelines in one automated industry surpassed the guidelines for fungi. Seasonal influence on viable microbial contamination including fungi with reduced susceptibility to the tested azoles was observed, besides the observed reduced susceptibility of pathogens of critical priority (Mucorales and Fusarium sp.). Aspergillus sections with potential toxigenic effect and with clinical relevance were also detected in all the sampling methods. Discussion The results regarding skin-biota in both controls´ and workers´ hands claim attention for the possible exposure due to hand to face/mouth contact. This study allowed concluding that working in automated and manual waste sorting plants imply high exposure to microbial agents.